EVALUASI WAKTU SIKLUS MENGGUNAKAN METODE MKJI 1997 (Studi Kasus Simpang Empat Macan Lindungan Kota Palembang) - Felly Misdalena; Hariman Alfaritzie (Fakultas Teknik Universitas Tridinanti, 2025)
The Macan Lindungan intersection in Ilir Barat I sub-district is a type 424 signalized intersection (4 arms, 2 minor road lanes and 4 3 major road lanes) with quite heavy traffic volume. But as time goes by and the number of vehicles continues to increase, traffic problems will arise. The emergence of traffic problems tends to result in traffic disorder. In this research, the author raised the topic of Cycle Time Evaluation Using the 1997 MKJI Method (Case Study of the Simpang Empat Macan Protected City of Palembang).The results of the analysis of intersection performance using the 1997 MKJI method, obtained a degree of saturation value of <0,85 at the four of intersection legs. The average delay value at the Macan Lindungan signalized intersection is 69.65 in the service level category E, with information about forced traffic flow (congested and continuous queues). The results of manual calculations on the new cycle time, by changing the cycle time to 110 seconds from the previous 163 seconds.